1991
DOI: 10.1093/carcin/12.1.83
|View full text |Cite
|
Sign up to set email alerts
|

The role of O6-alkylguanine in cell killing and mutagenesis in Chinese hamster ovary cells

Abstract: Chinese hamster ovary cells with no detectable (less than 200 molecules/cell) O6-methylguanine-DNA methyltransferase (EC 2.1.1.63) were transfected with human cell DNA and pSV2neo plasmid by electroporation. Two stable transformant clones, GC-1 and GC-2, containing 4 X 10(4) and 4-6 X 10(3) methyltransferase molecules/cell respectively were isolated by successive screening in the presence of G418 and 2-chloroethyl-N-nitrosourea (CNU). Only three or four copies of pSV2neo DNA and no repetitive human DNA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
9

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 0 publications
0
20
0
9
Order By: Relevance
“…It seems reasonable that this partial blockage may be related to the lethality ascribed to m6G in vivo (6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It seems reasonable that this partial blockage may be related to the lethality ascribed to m6G in vivo (6)(7)(8)(9)(10)(11)(12).…”
Section: Discussionmentioning
confidence: 99%
“…However, m6G is also capable of pairing with cytosine, in which case no mutation would result (1). In addition, there is evidence that m6G is a lethal lesion in eukaryotic and prokaryotic cells (6)(7)(8)(9)(10)(11)(12). These data raise the question of how this simple modification ofguanine can generate such different biological end points.…”
mentioning
confidence: 99%
“…Whatever the explanation for its mechanism, there clearly exists a means of amplifying the DNA synthesis inhibitory effects of relatively minor amounts of DNA damage. Models of methylation tolerance It has been suggested that tolerance may result from an enhanced ability to repair methylation lesions in DNA other than 06-meGua (24,62,87). While the apparent recessive nature of the tolerant phenotype would indicate otherwise, and the circumstantial evidence linking 06-meGua to cytotoxicity is strong, a definite answer to this question awaits a molecular characterization of tolerance.…”
Section: -Megua and Mutation Inductionmentioning
confidence: 99%
“…Such adducts are major contributors to the toxicity of alkylating anti-tumour agents, such as procarbazine, temozolomide, carmustine and related nitrosoureas commonly used for the treatment of several tumours (Schold et al, 1989;Dunn et al, 1991;Egyhazi et al, 1991;Brent et al, 1993;Marathi et al, 1993).…”
mentioning
confidence: 99%